2018
DOI: 10.1097/01.aoa.0000542359.79329.36
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring in Pregnant Women With Type 1 Diabetes (CONCEPTT): A Multicentre International Randomized Controlled Trial

Abstract: (Lancet 2017;390:2347–2359) Pregnant women with type 1 diabetes are at increased risk of preeclampsia, cesarean delivery, congenital anomalies, and other adverse pregnancy outcomes. While optimal glycemic control during pregnancy can improve outcomes, it is difficult to accomplish due to the complexity of insulin dose adjustments, changes in insulin sensitivity, and variability of insulin absorption that all occur during pregnancy. Continuous glucose monitoring (CGM) has been successful at improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(119 citation statements)
references
References 0 publications
4
109
2
4
Order By: Relevance
“…Second, the small sample size of this phase 2a study meant that we lacked statistical power for anything other than the power calculation assumption of a 30% between-group difference. Recent results from a CGM trial in 215 T1D pregnancies suggested that even small differences (a 7% increase in time in target and 5% reduction in hyperglycemia in the Continuous Glucose Monitoring in Pregnant Women With Type 1 Diabetes Trial [CONCEPTT]) are associated with substantial (;50%) reductions in neonatal complications (5). The current study was underpowered to detect small differences.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Second, the small sample size of this phase 2a study meant that we lacked statistical power for anything other than the power calculation assumption of a 30% between-group difference. Recent results from a CGM trial in 215 T1D pregnancies suggested that even small differences (a 7% increase in time in target and 5% reduction in hyperglycemia in the Continuous Glucose Monitoring in Pregnant Women With Type 1 Diabetes Trial [CONCEPTT]) are associated with substantial (;50%) reductions in neonatal complications (5). The current study was underpowered to detect small differences.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, the primary focus of treatment in a T1D pregnancy is to reduce fetal exposure to hyperglycemia without increasing maternal hypoglycemia. Recent evidence has suggested that although continuous glucose monitoring (CGM) improves day-to-day glucose control, with ;1 h/day less hyperglycemia in women who use multiple daily injections (MDIs) and continuous subcutaneous insulin infusion (CSII), optimal maternal glycemia is not achieved (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous studies of CGM in pregnancy. [43][44][45][46][47][48] Use of CGM during pregnancy has been reported to improve quality of glycemic control, but does not reduce the risk of macrosomia. 46,47 Additional randomized trials have been initiated.…”
Section: Cgm Studies In Special Populationsmentioning
confidence: 99%
“…46,47 Additional randomized trials have been initiated. 48 Hospitalized patients. Usage of CGM in the hospitalized patient and in the ICU remains a work in progress.…”
Section: Cgm Studies In Special Populationsmentioning
confidence: 99%